Management strategy for pink bollworm (Pectinophora gossypiella) in cotton (Gossypium hirsutum) in farmers-participatory mode - BIRAH, AJANTA; KUMAR, ANOOP; KHOKHAR, M K; SINGH, S P; MITKARI, A G; VARSHNEY, RICHA; NAVIK, OMPRAKASH; CHANDER, SUBHASH (The Indian Journal of Agricultural Sciences, 2023)
Cotton (Gossypium hirsutum L.) in central India is witnessing increasing infestation of bollworm and sucking pests since 2016. In recent years, pink bollworm, Pectinophora gossypeilla (Saunders) has emerged as a serious problem causing severe damage to cotton in several parts of our country. Farmers rely on chemical pesticides to control pest incidence that adversely affects naturally occurring predators and parasitoids in the crop ecosystems. The study was conducted by ICAR-National Research Centre for Integrated Pest Management, New Delhi during rainy (kharif) season 2018–21 to implement IPM validation trials at Wakhari village of Jalna district, Maharashtra with a view to study the economic viability and feasibility of adaptable IPM technology in farmer participatory mode. IPM implementation significantly reduced the number of insecticidal sprays (49.74%) and increased the cotton yield (28.49%) against the farmer’s practice (FP). Benefit to cost ratio was also higher in IPM fields (1.7, 2.4, 2.3 and 3.96) as compared to FP (1.3, 1.5, 1.74 and 2.97) during 2018, 2019, 2020 and 2021, respectively. It was evident that by adopting IPM strategy, pink bollworm in cotton can be successfully managed with minimum application of insecticides along with conservation of natural enemies and higher net return (42.6%) over farmer’s practice. The technology will be helpful in increasing the seed cotton yield and improve quality especially in terms of reduced pesticides contents, thereby improving the socio-economic status of cotton growers of the country.